Analysis of Imperative Utterances and Subtitle Translation in Devina Hermawan’s YouTube Videos - Ade Vania Ramadina; Nidia Sofa2 (Journal of Innovation Research and Knowledge, 2026)
This study aims to identified the illocutionary force of imperative utterances, the subtitling strategies used to translate them, and the translation accuracy of the English subtitles in Devina Hermawan's YouTube videos. This study used a descriptive qualitative method. The data consisted of 108 Indonesian imperative utterances collected from five of the most-viewed videos in the Indonesian Cuisine playlist. The utterances were classified using Quirk et al.'s (1985) theory of the illocutionary force of imperatives, while Gottlieb's (1992) subtitling strategies were applied to identify the strategies used to translate the subtitles. Translation accuracy was evaluated using Nababan et al.'s (2012) assessment model through Focus Group Discussion involving two raters. The findings reveal that Instruction is the dominant illocutionary force, followed by Advice or Recommendation and Suggestion. Eleven subtitling strategy patterns were identified, with Paraphrase and Transfer occurring most frequently. Furthermore, the subtitles achieved an average translation accuracy score of 2.9, indicating that most imperative utterances were translated accurately while preserving their communicative function. These findings indicate that the English subtitles generally preserve the intended meaning and communicative function of the source utterances, while the dominance of Instruction reflects the procedural characteristics of cooking tutorial videos and the predominance of Paraphrase demonstrates the translator's effort to produce natural and comprehensible subtitles for international audiences. This study contributes to audiovisual translation research by explaining the relationship between imperative functions, subtitling strategies, and translation accuracy in YouTube instructional videos.